Dental students’ perception of the use of instructional videos as an educational tool - Pacheco Filho, Antonio Carlos; Lopes Junior, Antônio; Thomes, Caroline Rodrigues; Garbin, Cléa Adas Saliba; Pacheco, Karina Tonini dos Santos (Brazilian Journal of Dental Education, 2026)
This study aimed to analyse dental students’ perceptions of instructional videos as a didactic-pedagogical resource. A video on syphilis and its oral manifestations was created for this purpose and shown to first- to third-year dental students at a Federal University in Brazil, who then responded to a semi-structured questionnaire with closed-ended questions. The results indicated that 56 students (88.89%) agreed the video effectively facilitated content comprehension, while 60 students (95.24%) fully agreed that it enhanced their understanding of the professor’s explanation. Furthermore, 50 students (79.37%) fully agreed that the video supported discussions during in-person activities. However, 28 students (44.45%) either partially or completely disagreed with the notion that the video could replace the professor’s presence in the classroom. In conclusion, instructional videos are an effective educational tool in dental education, improving learning outcomes, though in-person instruction remains essential for certain learning aspects.